High frequencies of nonviral colds and respiratory bacteria colonization among children in rural Western Uganda - Weary, Taylor E.; Pappas, Tressa; Tusiime, Patrick; Tuhaise, Shamilah; Ross, Elizabeth; Gern, James E.; Goldberg, Tony L. (Frontiers in Pediatrics, 2024)
Introduction Respiratory illness is the most common childhood disease globally, especially in developing countries. Previous studies have detected viruses in approximately 70-80% of respiratory illnesses. Methods In a prospective cohort study of 234 young children (ages 3-11 years) and 30 adults (ages 22-51 years) in rural Western Uganda sampled monthly from May 2019 to August 2021, only 24.2% of nasopharyngeal swabs collected during symptomatic disease had viruses detectable by multiplex PCR diagnostics and metagenomic sequencing. In the remaining 75.8% of swabs from symptomatic participants, we measured detection rates of respiratory bacteria Haemophilus influenzae, Moraxella catarrhalis, and Streptococcus pneumoniae by quantitative PCR. Results 100% of children tested positive for at least one bacterial species. Detection rates were 87.2%, 96.8%, and 77.6% in children and 10.0%, 36.7%, and 13.3% for adults for H. influenzae, M. catarrhalis, and S. pneumoniae, respectively. In children, 20.8% and 70.4% were coinfected with two and three pathogens, respectively, and in adults 6.7% were coinfected with three pathogens but none were coinfected with two. Detection of any of the three pathogens was not associated with season or respiratory symptoms severity, although parsing detection status by symptoms was challenged by children experiencing symptoms in 80.3% of monthly samplings, whereas adults only reported symptoms 26.6% of the time. Pathobiont colonization in children in Western Uganda was significantly more frequent than in children living in high-income countries, including in a study of age-matched US children that utilized identical diagnostic methods. Detection rates were, however, comparable to rates in children living in other Sub-Saharan African countries. Discussion Overall, our results demonstrate that nonviral colds contribute significantly to respiratory disease burden among children in rural Uganda and that high rates of respiratory pathobiont colonization may play a role. These conclusions have implications for respiratory health interventions in the area, such as increasing childhood immunization rates and decreasing air pollutant exposure.